The Conceptualization of a Week in the Contemporary Polish Language - Szadura, Joanna (Respectus Philologicus, 2014)
A week is a very special measure of time. It combines influences from numerous cultures and religions, and reveals a level of evolving knowledge about the world (mainly astronomical). Some researchers distinguish three basic systems of the conceptualization of a week: planetary (Babylonian), sacred (related to the Old and New Testament), and Slavic, which innovates in acknowledging Monday as the first day of the week. Researchers who claim that there is no explicit evidence to recognize the existence of a Slavic, pre-Christian seven-day week do not agree with this standpoint. The presented analysis is part ofthe above discussion and makes use of the historical linguistic context and contemporary language material. Based on survey statements, three versions of the Polish concept of week have been reconstructed, segmented as follows: (1) from the point of view of a person for whom Monday, as the Day of Resurrection (the most important holiday for Christians), begins the week; (2) from the point of view of a person for whom Sunday, as a holiday and a day off work, is an analogy to the seventh day during which God rested after creating the world and therefore ends the week; and (3) from the point of view of a person who works or studies beginning on Monday and rests on Sunday, but who does not invoke the religious aspect of the system but rather its social nature. The forms of conceptualization of week correspond to two attitudes, religious and secular (of which secural is currently dominant), and to transformations in Polish social life.
Keywords: linguistic picture of the world; linguistic and cultural categories; the concept of a week; contemporary Polish language